The Role of Islamic Economics in Promoting a Green and Sustainable Economy - Ridha, Fahrul (Yayasan Rahmat Islamiyah, 2025)
The purpose of this study is to comprehensively explain how Islamic economics can play a role in promoting a green economy and sustainable development. The focus will be on the basic principles of Islamic economics, best practices that have been implemented in various countries, and the challenges that must be overcome to integrate these two approaches harmoniously. This study uses a qualitative research method based on library research. The results of this study are that Islamic economics has a strategic role in promoting the realization of a green and sustainable economy through the principles of ethics, justice, and social responsibility that are in line with the goals of environmental conservation and community welfare. Instruments such as zakat, waqf, green sukuk, and profit-sharing financing can be optimized to finance environmentally friendly projects and empower communities inclusivel.